Major histocompatibility complex genomic investigation of endangered Chinese alligator provides insights into the evolution of tetrapod major histocompatibility complex and survival of critically bottlenecked species - He, Ke; Zhu, Ying; Yang, Shang-Chen; Ye, Qing; Fang, Sheng-Guo; Wan, Qiu-Hong (Frontiers in Ecology and Evolution, 2022)
The MHC gene family, a vital immune gene family in vertebrates, helps animals defend against pathogens. The polymorphism of MHC genes is important for a species and is considered to be caused by the numerous alleles of MHC antigen-presenting genes. However, the mechanism of this process is unclear due to the lack of data on the MHC structure. The evolutionary trajectories of the tetrapod MHC are also unclear because of insufficient studies on the reptile MHC architecture. Here, we studied the Chinese alligator (Alligator sinensis), which experienced a population bottleneck, but the population increased rapidly in the past thirty years and is proposed to have a unique MHC system to face pathogenic challenges. We successfully constructed a 2 Mb MHC region using BAC library and genome data of the Chinese alligator and checked the antigen-presenting genes using transcriptome data and RACE technique. The MHC architecture reported here uncovers adjacent Class I and Class II subregions and a unique CD1 subregion. This newly added information suggested that the Class I-II structure pattern was more ancient in tetrapods and helped reconstruct the evolution of the MHC region architecture. We also found multiple groups of MHC-I (12 duplicated loci, belonging to three groups, two of which were novel) and MHC-II (11 duplicated loci, belonging to two groups) inside the 2 Mb MHC region, and there were three more duplicated MHC-I loci outside it. These highly duplicated antigen-presenting loci had differences in expression, amino acid length of antigen-presenting exons, and splice signal of exon and intron, which together promoted the polymorphism of duplicated genes. Although the MHC antigen-presenting genes were identified as monomorphic or oligomorphic in our previous population study, the loci with high copy numbers and many differences can make up for this loss, presenting another mechanism for polymorphism in antigen presentation. To summarize, the fine MHC region architecture of reptiles presented in this study completes the evolutionary trajectories of the MHC structure in tetrapods, and these distinctive MHC gene groups in the Chinese alligator may have helped this species to expand rapidly in the past recent years.